Proteus sp. – an opportunistic bacterial pathogen – classification, swarming growth, clinical significance and virulence factors - Różalski, Antoni; Torzewska, Agnieszka; Moryl, Magdalena; Kwil, Iwona; Maszewska, Agnieszka; Ostrowska, Kinga; Drzewiecka, Dominika; Zabłotni, Agnieszka; Palusiak, Agata; Siwińska, Małgorzata; et al. (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2012)
The genus Proteus belongs to the Enterobacteriaceae family, where it is placed in the tribe Proteeae, together with the genera Morganella and Providencia. Currently, the genus Proteus consists of five species: P. mirabilis, P. vulgaris, P. penneri, P. hauseri and P. myxofaciens, as well as three unnamed Proteus genomospecies. The most defining characteristic of Proteus bacteria is a swarming phenomenon, a multicellular differentiation process of short rods to elongated swarmer cells. It allows population of bacteria to migrate on solid surface. Proteus bacteria inhabit the environment and are also present in the intestines of humans and animals. These microorganisms under favorable conditions cause a number of infections including urinary tract infections (UTIs), wound infections, meningitis in neonates or infants and rheumatoid arthritis. Therefore, Proteus is known as a bacterial opportunistic pathogen. It causes complicated UTIs with a higher frequency, compared to other uropathogens. Proteus infections are accompanied by a formation of urinary stones, containing struvite and carbonate apatite. The virulence of Proteus rods has been related to several factors including fimbriae, flagella, enzymes (urease - hydrolyzing urea to CO2 and NH3, proteases degrading antibodies, tissue matrix proteins and proteins of the complement system), iron acqusition systems and toxins: hemolysins, Proteus toxin agglutinin (Pta), as well as an endotoxin - lipopolysaccharide (LPS). Proteus rods form biofilm, particularly on the surface of urinary catheters, which can lead to serious consequences for patients. In this review we present factors involved in the regulation of swarming phenomenon, discuss the role of particular pathogenic features of Proteus spp., and characterize biofilm formation by these bacteria.